2021
DOI: 10.1111/inr.12682
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 impact on nurses in Spain: a considered opinion survey

Abstract: Aim: To survey nurses' opinions about their work conditions at the onset of the COVID-19 pandemic in Spain. Background: For the Spanish General Council of Nursing (the Consejo General de Enfermer ıa de España), it was essential to have information on nursing workforce conditions and nurses' preparedness to wear protective measures at the pandemic's onset. The coronavirus outbreak was believed to have started in China and rapidly spread as a global pandemic requiring policies and actions for planning emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
0
20
0
4
Order By: Relevance
“…The feeling of being pushed outside of society seems to contradict the common perception of healthcare workers being seen as heroes during the pandemic. Other studies conducted in Spain, Italy and USA reported that nurses do not want to be perceived as heroes and receive applause from balconies, but they look for recognition of their hard work and improvements to their working conditions (Fontanini et al., 2021; Labrague & Santos, 2020; Perez‐Raya et al., 2021; Shah et al., 2021; Turale & Nantsupawat, 2021). Similarly, the ICU nurses in this study expressed that they want to be valued and financially compensated for their hard work and the work‐related risks they encounter.…”
Section: Discussionmentioning
confidence: 99%
“…The feeling of being pushed outside of society seems to contradict the common perception of healthcare workers being seen as heroes during the pandemic. Other studies conducted in Spain, Italy and USA reported that nurses do not want to be perceived as heroes and receive applause from balconies, but they look for recognition of their hard work and improvements to their working conditions (Fontanini et al., 2021; Labrague & Santos, 2020; Perez‐Raya et al., 2021; Shah et al., 2021; Turale & Nantsupawat, 2021). Similarly, the ICU nurses in this study expressed that they want to be valued and financially compensated for their hard work and the work‐related risks they encounter.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that Spain already had a worrying shortage of nurses before the pandemic, as it had a 31% deficit in the number of nurses compared with the average for the European Union (574 vs 802 nurses/100, 000 inhabitants) (Arévalo‐Manso, 2019 ). The pandemic has further aggravated the situation due to the high number of patients infected with COVID‐19 (ECDC, 2021 ), along with the shortage of nurses and deficiencies in health services (Castro‐Sánchez & Santillán‐García, 2020 ), increased job demands and workload, resulting in distress and a significant psychological impact on nurses (Pérez‐Raya et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the metaanalysis carried out by Gholami included 119,883 healthcare workers infected with SARS-CoV-2 and that carried out by Gómez-Ochoa included 96,813; whereas the Peruvian health worker cohort alone included 90,672 infected healthcare workers. This shows in absolute terms the great affectation of Peruvian healthcare workers by the pandemic, not only due to the high workload, continuous exposure, and lack of personal protective equipment (mainly at the beginning of the pandemic); but also due to the informal nature of work and the worsening labor conditions observed in various countries since before the pandemic, particularly those with low and medium income [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%